Ferroptosis and iron metabolism in diabetes: Pathogenesis, associated complications, and therapeutic implications - Jin, Eun-Ju; Jo, Yunju; Wei, Shibo; Rizzo, Manfredi; Ryu, Dongryeol; Gariani, Karim (Frontiers in Endocrinology, 2024)
Diabetes mellitus is a complex chronic disease, considered as one of the most common metabolic disorders worldwide, posing a major threat to global public health. Ferroptosis emerges as a novel mechanism of programmed cell death, distinct from apoptosis, necrosis, and autophagy, driven by iron-dependent lipid peroxidation accumulation and GPx4 downregulation. A mounting body of evidence highlights the interconnection between iron metabolism, ferroptosis, and diabetes pathogenesis, encompassing complications like diabetic nephropathy, cardiomyopathy, and neuropathy. Moreover, ferroptosis inhibitors hold promise as potential pharmacological targets for mitigating diabetes-related complications. A better understanding of the role of ferroptosis in diabetes may lead to an improvement in global diabetes management.In this review, we delve into the intricate relationship between ferroptosis and diabetes development, exploring associated complications and current pharmacological treatments.